Big love. The complete first season [videorecording (DVD)] - Paxton, Bill; Sevigny, Chloë; Tripplehorn, Jeanne, 1963-; Goodwin, Ginnifer; Stanton, Harry Dean, 1926-2017; Dern, Bruce (Big love (Television program), 2006)
A polygamist and independent businessman lives in Salt Lake City with his three wives and seven children. He faces many challenges in meeting the emotional, romantic, and financial needs of his wives.